Chronic Diarrhea as the Sole Symptom of HIV Infection: A Case Report - mehdi alimadadi; sina Mohajernoei; hanieh Raghimi (Journal of Clinical and Basic Research, 2021)
Background: Acquired immunodeficiency syndrome (AIDS) is a disease caused by the human immunodeficiency virus (HIV) that can affect all systems of the human body. Considering that there is no definitive treatment for AIDS, timely and accurate diagnosis is important. Symptoms of HIV infection may sometimes be nonspecific and should always be considered in high-risk individuals. We herein report a patient with HIV who was presented with chronic diarrhea as the sole symptom of HIV Infection. Case description: A 40 years old man was admitted to hospital with complain of diarrhea that had started seven months ago. He also experienced extensive weight loss and complained of vomiting and abdominal pain in the past month without any fever. Abdominal computed tomography scan and colonoscopy and stool examination were normal. However, biopsy indicated active colitis. Laboratory tests for HIV, functional expression of the lymphoid chemokines, and anti-tissue transglutaminase antibody were negative, but hepatitis C viral load was positive. Because the patient had many tattoos on his body that were done in unsanitary places, AIDS was suspected. The related test was requested, and the result was positive. Finally the patient was prescribed with co-trimoxazole and referred to an AIDS consultation center. Conclusion: We presented a case of HIV infection with chronic diarrhea as the only symptom without any others clinical findings. Our observations suggest that for better diagnosis and management of HIV infection, it is important to consider chronic diarrhea as one of the important complications of HIV even when not accompanied with any other symptom.